Nosná železobetonová konstrukce administrativní budovy - Kroček, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Bakalářská práce se zabývá řešením nosné železobetonové konstrukce administrativní budovy. V první části práce jsou stanoveny vnitřní síly výpočetním softwarem, které jsou dále použity pro dimenzování lokálně podepřené stropní desky nad 1.NP a charakteristického sloupu. Správnost výpočtu je potvrzena metodou rámových výseků s využitím deformační metody. Druhá část řeší posouzení konstrukcí na mezní stav únosnosti v souladu s ČSN EN 1992-1-1. V závěru jsou zpracovány výkresy tvaru a výztuže stropní desky a charakteristického sloupu.

The bachelor's thesis deals with the solution of the load-bearing reinforced concrete structure of an administrative building. In the first part of the work, the internal forces are determined by computer software, which are further used for dimensioning the locally supported ceiling slab above the 1st floor and the characteristic column. The accuracy of the calculation is confirmed by the method of frame cut-outs using the deformation method. The second part deals with the assessment of structures for the ultimate limit state in accordance with ČSN EN 1992-1-1. Finally, drawings of the shape and reinforcement of the ceiling slab and the characteristic column are processed.
The load-bearing reinforced concrete structure of an administrative building
Keywords: lokálně podepřená stropní deska; sloup; ČSN EN 1992-1-1; metoda rámových výseků; mezní stav únosnosti; železobeton; locally supported ceiling slab; column; ČSN EN 1992-1-1; method of frame cut-outs; ultimate limit state; reinforced concrete